ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH PADA KESETIAAN PASIEN DI RUMAH SAKIT SURAKARTA - Amelia Putri; Waluyo Budi Atmoko; Nang Among Budiadi (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
This research is pur posed to testing the loyalty of the ppatients that affected by pat ients satisfaction through commitment mediation, confiedence, and hospital image that moderating the relationship between consumer satisfactions and confidences. Data obtained from questionraires that shared to hospitalized patients at Hermina Hospital. The collecting samples technique used the pur posive sampling technique with 200 patient respondents that hospitalized at Hermina Hospital. Hypothetical test were done by using SEM analytic and Regression. This research shows that commitment are significantly affect patien loyalties, loyalties variable significantly affect commitment, variable isn’t moderating the connection between patient satisfactions th atpatient loyalties obliquely affected by patient satisfactions through commitment mediation.